Development and validation of knowledge and intention to breastfeed during pandemic questionnaire using exploratory factor analysis and rasch model - Muhd Helmi, Muhd Alwi; Mohd Nor, Mohd Zali; Tengku Ismail, Tengku Alina; Zainal Abidin, Muhammad 'Adil; Hasan, Taufiq Hidayat (Malaysian Public Health Physicians' Association, 2022)
Breastfeeding during the COVID-19 pandemic is challenging. Strong intention and good knowledge on the risk and benefit of breastfeeding are important for a woman to breastfeed her child during this period. This study aims to develop and validate a Malay language questionnaire in order to measure Malaysian women's knowledge and intention about breastfeeding during the pandemic. The items were developed based on an extensive review of literature as well as breastfeeding guidelines and suggestions from experts, followed by an assessment of content and face validity that involved nine and 30 reviewers respectively. A pilot study was conducted on 90 respondents and the reliability assessment was performed using Rasch analysis. Exploratory factor analysis (EFA) was used to determine the number of latent factors within the intention dimension. Among 29 knowledge items and 36 intention items, 19 knowledge items remained with a person separation (person reliability) as well as item separation (item reliability) of 1.73(0.75) and 3.97(0.94). The final intention domain had 17 items with a person separation (person reliability) as well as item separation (item reliability) of 1.54(0.70) and 3.87(0.94). Three latent factors were identified within the intention questionnaire. The final 17 items explained 53.7% of the variance with an overall Kaiser-Meyer-Olkin measure of sampling adequacy of 0.70, χ2 = 623.40 (136), p<0.001. Using the framework of the theory of planned behaviour, the drafted questionnaire is reliable and valid based on the Rasch measurement model to measure the knowledge and intention about breastfeeding during an infection outbreak.